Multi-objective optimization design of hydropneumatic suspension with gas–oil emulsion for ride comfort and handling stability of an articulated dumper truck. Issue 2 (1st February 2023) - Yang, Lin; Wang, Ruochen; Sun, Zeyu; Meng, Xiangpeng; Zhu, Zhihao
Abstract : This article presents the ride comfort and handling stability performance of an articulated dumper truck (ADT). Considering the influence of the hydropneumatic suspension (HPS) with gas–oil emulsion on the ADT, a comprehensive ADT dynamic model is proposed. Also, on the basis of the nonlinear programming quadratic line (NLPQL) algorithm, an integrated multi-objective optimization method regarding the HPS with gas–oil emulsion is proposed to improve the comfort and stability and ensure enough suspension working space. The body acceleration, roll angle and pitch angle of HPS are optimized to a higher degree by 17.2%, 18.4% and 23% (with no load) and 18.3%, 17.7% and 23.1% (with full load) under random excitation input. The simulation results show that the NLPQL optimization method not only increases the ride comfort and handling stability performance of ADT with reasonable suspension working space, but also helps to guide the design of the ADT's HPS system.